Konservasi Tanaman Pangan, Obat, dan Pewarna Berdasarkan Kearifan Lokal Masyarakat Desa Sesait, Kecamatan Kayangan, Kabupaten Lombok Utara - Jupri, Ahmad; Isrowati, Isrowati; Maulida, Baiq Rizki; Aini, Diah Kurotul; Rabani, M. Restu; Ichsani, Qatrunnadia; Ramadhani, Baiq Isna Rizka; Wirahadi, Muhammad Rosyid; Wulandari, Suci Yulia; Hidayati, Lilik (LPPM Universitas Mataram, 2025)
The history of Sesait Village, which used to be 90% of the Kayangan sub-district area. The tradition in Sesait Village is the rules for nurak like